Presentation of Infectious Keratitis to ED during COVID-19 Lockdown. (12th June 2021) - Power, Barry; Donnelly, Aaron; Murphy, Conor; Fulcher, Timothy; Power, William
Abstract : Objectives . To compare presentation of infectious keratitis during COVID-19 lockdown with previous years, assess relative severity, and compare outcomes between COVID-19 and pre-COVID-19 era groups. Methods . Acute presentations of infectious keratitis during a strict government-mandated COVID-19 lockdown period were analysed retrospectively (March–May 2020). Data were compared with the same periods in 2018-2019. The clinical notes of patients undergoing corneal scrapes were reviewed, and data were collected on treatment, culture growth, surgical interventions, visual outcomes, admission rates, and risk factors. Results . There were 37% fewer presentations of infectious keratitis to the ED in 2020 ( N = 29, 47, and 45, respectively). Risk factor profiles and microbial data were similar across all periods. Admission rates and use of fortified antibiotics were lower in 2020. COVID-19 era cases recovered less vision (LogMAR 0.26, 0.67, and 0.45, respectively; p = 0.04) and were more likely to require surgical intervention (10%, 4%, and 2%, respectively; OR 3.4 (CI 0.7–17.9, p = 0.1)). Conclusion . A concerning fall in presentations of infectious keratitis to ED during the pandemic lockdown was observed. Though societal behaviour changed during the lockdown, our data suggest it is unlikely that the incidence of infectious keratitis fell significantly. It is unclear how and where these patients were treated. We postulate that lower levels of visual recovery and higher rates of surgical intervention may have been caused by delays in accessing care. To minimise avoidable ocular morbidity as COVID-19 resurges, we must communicate clearly with patients and health professionals on how to access available emergency eye care services.